Establishing the Tallgrass Prairie National Preserve - Jim Hoy (Symphony in the Flint Hills, 2015)
Efforts to establish some sort of national prairie park go back to the 1920s. In 1930 Victor E. Shelford of the University of Illinois proposed that a large area of grassland on the Nebraska-South Dakota border be taken into the national park system. His suggestion went unheeded, and it was not until the later 1950s that interest again began to grow
Keywords: tallgrass; prairie; plains; Flint Hills; Kansas; National parks; preserves; native; history; legislation; public; private; partnership; care; folklife